The book of Haggai : prophecy and society in early Persian Yehud - Kessler, John, 1951- (Supplements to Vetus Testamentum,, 2002)
This monograph is a study of the perceptions reflected in the Book of Haggai regarding the primary social, political and religious institutions in early Persian Yehud. Special attention is given to the form and function of prophecy, and to the role of the prophet in society. The study includes a history of the criticism of Haggai, a study of the book's redactional history and socio-political context, and an exegesis and literary analysis of the text. It concludes with an examination of the distinctive perspectives found in the book and the sociological and religious milieu that produced them. The work is particularly useful for its detailed analysis of the biblical text, its attention to recent literature on the early Persian period, and its multidisciplinary and integrative approach.